2021
DOI: 10.1002/pmrj.12715
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation perceptions and experiences of physiatrists in a lower‐middle‐income country during the COVID‐19 pandemic

Abstract: Background The COVID‐19 pandemic catalyzed the adoption of telerehabilitation in various health care settings. However, there was neither a preexisting national guideline in the Philippines nor an internationally agreed upon standard for telerehabilitation. The literature lacks nationwide studies documenting how physiatrists perceived and experienced telerehabilitation during the pandemic. Objective To determine the perceptions and experiences of physiatrists in the Philippines regarding telerehabilitation. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…This knowledge is needed among the first priorities identified by the patients and clinicians after COVID-19 widely affected the delivery of rehabilitation services. 92 , 93 63.6% of the retrieved manuscript reported on randomized controlled trials demonstrating the current need for evidence about the effectiveness of telemonitoring and telerehabilitation in patients with chronic lung diseases or COVID-19. This paper presented the evidence available as of June 2021.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge is needed among the first priorities identified by the patients and clinicians after COVID-19 widely affected the delivery of rehabilitation services. 92 , 93 63.6% of the retrieved manuscript reported on randomized controlled trials demonstrating the current need for evidence about the effectiveness of telemonitoring and telerehabilitation in patients with chronic lung diseases or COVID-19. This paper presented the evidence available as of June 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported rehabilitation for patients with COVID-19 pneumonia ( 14 18 ). However, to the best of our knowledge, there have been no reports of rehabilitation for patients with MIS-C.…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm shift may even continue beyond the pandemic period after the telemedicine stakeholders (consumers and providers) have begun to realize the benefits of virtual care and how to mitigate its inherent limitations and risks (e.g., data privacy issues, technical difficulties, challenges in virtual examination). 14,17 To sustain eHealth in the country, the National Telehealth Center (NTTC) of the Philippines as the lead government agency, will need to push for the institutionalization of an eHealth structure and eHealth system. 18 However, similar to other resource-limited countries, even after almost two years into the pandemic, telemedicine is still poorly integrated with the Philippines' health care and educational system due to various challenges.…”
Section: Discussionmentioning
confidence: 99%